Homology of the enigmatic nuchal bone reveals novel reorganization of the shoulder girdle in the evolution of the turtle shell. Issue 5 (16th September 2013) - Lyson, Tyler R.; Bhullar, Bhart‐Anjan S.; Bever, Gabe S.; Joyce, Walter G.; de Queiroz, Kevin; Abzhanov, Arhat; Gauthier, Jacques A.
SUMMARY The turtle shell represents a unique modification of the ancestral tetrapod body plan. The homologies of its approximately 50 bones have been the subject of debate for more than 200 years. Although most of those homologies are now firmly established, the evolutionary origin of the dorsal median nuchal bone of the carapace remains unresolved. We propose a novel hypothesis in which the nuchal is derived from the paired, laterally positioned cleithra—dorsal elements of the ancestral tetrapod pectoral girdle that are otherwise retained among extant tetrapods only in frogs. This hypothesis is supported by origin of the nuchal as paired, mesenchymal condensations likely derived from the neural crest followed by a unique two‐stage pattern of ossification. Further support is drawn from the establishment of the nuchal as part of a highly conserved "muscle scaffold" wherein the cleithrum (and its evolutionary derivatives) serves as the origin of the Musculus trapezius. Identification of the nuchal as fused cleithra is congruent with its general spatial relationships to other elements of the shoulder girdle in the adult morphology of extant turtles, and it is further supported by patterns of connectivity and transformations documented by critical fossils from the turtle stem group. The cleithral derivation of the nuchal implies an anatomical reorganization of the pectoral girdle in which the dermal portion of the girdle was transformed from a continuous lateral‐ventral arc into separate dorsal and ventral components. This transformation involved the reduction and eventual loss of the scapular rami of the clavicles along with the dorsal and superficial migration of the cleithra, which then fused with one another and became incorporated into the carapace.